C-reactive protein point-of-care testing in primary care—broader implementation needed to combat antimicrobial resistance - Llor, Carl; Plate, Andreas; Bjerrum, Lars; Gentile, Ivan; Melbye, Hasse; Staiano, Annamaria; van Hecke, Oliver; Verbakel, Jan Y.; Hopstaken, Rogier (Frontiers in Public Health, 2024)
This study presents the perspective of an international group of experts, providing an overview of existing models and policies and guidance to facilitate a proper and sustainable implementation of C-reactive protein point-of-care testing (CRP POCT) to support antibiotic prescribing decisions for respiratory tract infections (RTIs) with the aim to tackle antimicrobial resistance (AMR). AMR threatens to render life-saving antibiotics ineffective and is already costing millions of lives and billions of Euros worldwide. AMR is strongly correlated with the volume of antibiotics used. Most antibiotics are prescribed in primary care, mostly for RTIs, and are often unnecessary. CRP POCT is an available tool and has been proven to safely and cost-effectively reduce antibiotic prescribing for RTIs in primary care. Though established in a few European countries during several years, it has still not been implemented in many European countries. Due to the complexity of inappropriate antibiotic prescribing behavior, a multifaceted approach is necessary to enable sustainable change. The effect is maximized with clear guidance, advanced communication training for primary care physicians, and delayed antibiotic prescribing strategies. CRP POCT should be included in professional guidelines and implemented together with complementary strategies. Adequate reimbursement needs to be provided, and high-quality, and primary care-friendly POCT organization and performance must be enabled. Data gathering, sharing, and discussion as incentivization for proper behaviors should be enabled. Public awareness should be increased, and healthcare professionals’ awareness and understanding should be ensured. Impactful use is achieved when all stakeholders join forces to facilitate proper implementation.